СТРУКТУРА РУСЛОВЫХ РАЗВЕТВЛЕНИЙ - Алексеевский Н.И.; Чалов С.Р. (My University, 2004)
Quantitative criteria of channel furcations structure are discussed. According to these criteria furcated channels of different types under various natural conditions were analysed. Among the factors of furcation the most important one is the excess of actual solid runoff over the transport capacity of the flow.
Keywords: 551.435.11